3D Printed Multifunctional Self‐Adhesive and Conductive Polyacrylamide/Chitosan/Sodium Carboxymethyl Cellulose/CNT Hydrogels as Flexible Sensors. Issue 2 (4th December 2022) - Hao, Feiyue; Maimaitiyiming, Xieraili; Sun, Shuang
Abstract: 3D printing of hydrogels with improved mechanical properties will play an important role in many fields in the future. Polyacrylamide with controllable reaction conditions and chitosan with increased mechanical strength are chosen to prepare hybrid hydrogels with high mechanical properties (elongation >2000%). The addition of sodium carboxymethyl cellulose enables this hydrogel system to have excellent rheological properties for 3D printing. The samples prepared by 3D printing technology have larger elongation (>1000%) and higher elastic modulus (141.99 kPa). Carbon nanotube‐added composite hydrogels can be used to fabricate flexible electronic devices with diverse functions and structures. The prepared sensor can detect the signals of human movement (joint movement, breathing, drinking water), and has a sensitive signal response in the range of 12–67 °C. In addition, this sensor can also be extended to the application of NH3 gas signal sensing. Due to the stable performance and long service life of conductive multifunctional hydrogels, the application potential of hydrogel sensors will be further increased. In conclusion, this simple‐prepared 3D‐printable high‐mechanical‐performance hydrogel with multiple network crosslinks has a favorable competitive advantage in future flexible material applications. Abstract : Acrylamide/chitosan composite hydrogel with high tensile properties can be used to prepare hydrogel ink by introducing sodium carboxymethyl cellulose. In addition, the hydrogel exhibits better self‐adhesion after being immersed in sodium citrate. After the introduction of carbon nanotubes, a multifunctional sensor can be prepared by 3D printing for direct detection of human motion.